Chapter 11 and the level playing field: Should chapter 11 be considered as a subsidy?. (January 2019) - Bock, Sebastian; Forsyth, Peter; Niemeier, Hans-Martin; Mantin, Benny
Abstract: This paper assesses whether Chapter 11 is a form of subsidy for US airlines. US airlines have used Chapter 11 to restructure their operations. This has been criticized as a subsidy by major non US airlines and governments for a long time and recently, in the "level playing field" debate. Applying legal and economic perspectives of subsidy, we examine the different opportunities of Chapter 11 to reduce airlines' costs. It is argued that most of the forms available, such as the modification of collective bargaining, do not constitute a subsidy. Only the termination of pension plans might involve a subsidy, but only using a legal definition of doubtful relevance since there is normally no use of public funds. Highlights: Major non US airlines and governments criticize Chapter 11 as a subsidy. However, most of the forms of Chapter 11 do not constitute a subsidy. Even the termination of pension plans does not normally involve a subsidy.